2021
DOI: 10.1055/s-0040-1721065
|View full text |Cite
|
Sign up to set email alerts
|

Use of Homeopathy in Integrative Oncology in Strasbourg, France: Multi-center Cross-Sectional Descriptive Study of Patients Undergoing Cancer Treatment

Abstract: Context The use of homeopathy in oncological supportive care seems to be progressing. The first French prevalence study, performed in 2005 in Strasbourg, showed that only 17% of the subjects were using it. What is the situation 12 years later? Materials and Methods This is a descriptive study, using a questionnaire identical to that used in 2005, on 633 patients undergoing treatment in three anti-cancer centers in Strasbourg. The results of the “homeopathy” sub-group were extracted and studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…With a prevalence of 30.7%, homeopathy is the most used complementary medicine chosen by cancer patients in France, with an increased patients’ satisfaction [23]. Another French study based on the Nationwide Healthcare Database targeted all patients who underwent mastectomy for newly diagnosed breast cancer between 2012 and 2013 (98 009 patients).…”
Section: Complementary Approach: the Example Of Homeopathymentioning
confidence: 99%
“…With a prevalence of 30.7%, homeopathy is the most used complementary medicine chosen by cancer patients in France, with an increased patients’ satisfaction [23]. Another French study based on the Nationwide Healthcare Database targeted all patients who underwent mastectomy for newly diagnosed breast cancer between 2012 and 2013 (98 009 patients).…”
Section: Complementary Approach: the Example Of Homeopathymentioning
confidence: 99%
“…In Strasbourg, France, a recent study indicated that 30% of patients undergoing chemotherapy have recourse to it. 6 An learned society has been created, the International Homeopathic Society of Supportive Care in Oncology (IHSSCO), which publishes therapeutic recommendations. 7 HSC can improve the quality of life of patients 8 and consequently their survival.…”
Section: Interventions and Outcomesmentioning
confidence: 99%
“…It can improve the quality of life [3] and consequently the survival of the patients [4,5]. Well accepted by French oncologists and general practitioners [6], inexpensive [7], it is the complementary medicine most used in supportive care [8]. Homeopathic supportive care is provided in several cancer centres in France and other parts of Europe [9,10] and patient satisfaction rate is very high [8].…”
Section: Introductionmentioning
confidence: 99%
“…Well accepted by French oncologists and general practitioners [6], inexpensive [7], it is the complementary medicine most used in supportive care [8]. Homeopathic supportive care is provided in several cancer centres in France and other parts of Europe [9,10] and patient satisfaction rate is very high [8]. Combined with organotherapy and isotherapy, it can form essential supportive care to patients undergoing treatment with the new targeted therapies [11].…”
Section: Introductionmentioning
confidence: 99%